Investigation of Drinking Water Quality in Torbat Heydariyeh with IWQIS in 2018 - Mina Ghahrchi; Behnam Sepehrniya; Edris Bazrafshan; Tahereh Jahanara; Fatemeh Barjasteh; Mohammad Sarmadi (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: Assessment of water quality assessment is an appropriate measure an important step for the optimal and efficient use of drinking water resources. This study aimed to investigate of drinking water quality in Torbat Heydariyeh County using IWQIS software in 2018. Methods: In the present study, 234 samples of groundwater resources were taken from different areas of the city and 20 physicochemical parameters were evaluated. Drinking water quality and rating was estimated using the Iranian Water Quality Index Software (IWQIS) and statistical analysis was performed in SPSS software (version 20). Results: As evidenced by the obtained results, only about 1% of the samples were outside the standard range of drinking water quality, according to IWQIS software. Moreover, from all investigated samples, 9.2% in total soluble solids, 14.5% in magnesium, 8.6% in chlorine, 0.4% in nitrate, 42.1% in sodium, and 97% in fluoride were outside of Iran's national water standard No.1053. Conclusion: The average drinking water quality index (DWQI) in Torbat Heydariyeh was obtained at 46.76 which falls within an excellent range, excluding water fluoride. Moreover, the highest number of samples outside the standard range was observed in autumn.